Dr. Faustus as a Morality Play - Mariwan Hwayyiz Rustum (QALAAI ZANIST JOURNAL, 2022)
Dr. Faustus's tragic history embodies a play by Christopher Marlowe, in which a man sells his soul to the evil spirit for power and knowledge. The play begins with the hero at the height of his arrival and ends with his falling into grief, death and curse. Faust entered into a contract with Lucifer, 24 years of life on Earth will be allocated, during which time he will have Mephistopheles as his personal servant and attached to the use of magic; however, in the end, he will give his body and soul to Lucifer as a push and spend the rest of his time as a cursed man in hell. This transaction must be sealed in the form of a contract written in the blood of Faustus. After cutting off his arm, the wound heals divinely and the Latin words Homo, fuge! ("Man, run!") Then he shows up on it. Faust ignores the inscription while asserting that he has already cursed his actions so far, thus leaving nowhere to escape. Faust seems to repent in the end and regret his actions, yet it may be too late or irrelevant, because Mephistopheles takes his soul together, so Faust obviously goes to hell with him. The current research addressed "Dr. Faustus" as a morality play after explanation the importance of "morality play", and then its connection through this tragic drama.